Poor implementation of teaching material in the english language teaching-learning process on the students of senior year at Kleber Franco Cruz high school, academic year 2014-2015. - Correa Hidalgo, José Junior; Correa Rambay, Edwin Oscar; Villacrés Encarnación, Carlos Eduardo (Machala : Universidad Técnica de Machala, 2014)
El tema de esta tesis es el siguiente: Poor implementation in the use of teaching materials in the English language teaching-learning process on the students of Senior Year at Kleber Franco Cruz High School, academic year 2014-2015, el cual es de suma importancia porque los materiales didácticos son la herramienta ideal que los docentes necesitan para llevar una clase dinámica y clara para sus estudiantes. El problema central es la baja implementación en el uso de los materiales didácticos en el proceso de enseñanza – aprendizaje del idioma Inglés, esto ocasiona un bajo nivel de interés en los estudiantes. El objetivo general está en determinar cómo pueden ser aplicados los materiales didácticos en el proceso enseñanza-aprendizaje del idioma Inglés.
The topic of the thesis hereby is: Poor implementation of teaching material for the English language teaching-learning process on the students of Senior Year at Kleber Franco Cruz high school, academic year 2014-2015, which is highly relevant because teaching materials are the ideal tool that teachers need to carry out a dynamic and clear lesson for their students. The central problem is the poor implementation of teaching materials in the English language teaching-learning process. This decreases the interest of students to learn the language. The general objective of the thesis is to determine how teaching materials can be applied in the English language teaching-learning process.
Keywords: IMPLEMENTATION; LANGUAGE; MATERIAL